Managing workplace health and wellbeing during a crisis how to support your staff in difficult times - Cooper, Cary L.; Hesketh, Ian (London Kogan Page, 2022)
"During the Covid-19 pandemic, almost half of Americans reported that the crisis had a negative effect on their mental health. In the UK, the financial crisis of 2008 resulted in a rise in stress and anxiety and a decline in physical health. When dealing with a crisis, a business will consider the resilience of its structures and processes or the impact on forecasts and budgets but what about their people? Without a supported, engaged and motivated workforce, the business won't be able to achieve its crisis recovery plans. Managing Workplace Health and Wellbeing During a Crisis is a practical guide for all HR professionals and those responsible for talent management. It covers how to deal with employee stress and burnout as well as how to drive engagement, motivation and morale during unsettled times. There is expert guidance on how to deal with role and responsibility changes and explains how to improve productivity through effective employee communication. Supported by case studies from companies including Microsoft, Marks and Spencer, GlaxoSmithKline, Rolls-Royce and Twitter, this book equips readers to deal with a crisis as it is happening and implement longer term post-crisis strategies. Written by an expert author team including Professor Sir Cary Cooper, Chair of the National Board of Health and Wellbeing at Work, this is necessary reading for all professionals needing to deal with the health and wellbeing of their workforce in any crisis that may arise"--
Includes bibliographical references and index.
Keywords: COVID-19 (Disease); Crisis management; Employee motivation; Industrial hygiene; Job stress